Informal caregivers on home enteral nutrition need knowledge, skills and professional support - Peixoto, Anelisa Spinelli; Siqueira Vassimon, Helena (Revista de Medicina e Saúde de Brasília, 2015)
Objective: To assess effectiveness of informal caregivers in administering home enteral nutrition (HEN). Casuistic and Method: Patients scheduled for hospital discharge with the use of HEN were selected during hospitalization. Twenty-two patients and their caregivers were visited at home 4 days after discharge from the hospital. During the visit, the preparation and administration of 1 enteral feeding bottle by the caregiver were observed and possible mistakes made during the process were recorded. The quality of life of the caregivers was determined by applying the World Health Organization Quality of Life – Bref (WHOQOL Bref.) questionnaire and the nutritional status of the patients was analyzed by calculating the body mass index. Results: Most of the informal caregivers were unable to offer appropriate HEN. Ninety percent of them did not follow recommendations about hygiene such as hand asepsis or disinfection of the utensils and 70% did not prepare the enteral diet in an appropriate manner according to prescription and guidelines, using a smaller amount of the powdered diet and offering fewer calories to the patients (approximately 500 kcal/day). The caregivers themselves (73%) reported difficulties in understanding the instructions provided at discharge from the hospital and their quality of life was classified as medium-high. Most patients (59%) were found to be malnourished and had a calf circumference of less than 31 cm (73%). Conclusion: The caregivers were not efficient or effective in offering HEN and made mistakes during the process. Informal caregivers need homecare service for training and